Perancangan Sistem Transmisi Mesin Pencetak Bakso Kapasitas 250-280 Butir/Menit - Yefrizal Yefrizal; Nazaruddin Nazaruddin; Dedi Rosa Putra Cupu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The process of making meatballs is still using a very manual method that is by using the hand. Making manually requires a long time and is still doubtful about its cleanliness. One solution to this problem is to design a meatball molding that can help small businesses to produce more efficient and effective processed meatball production. The results of designing a molding machine for meatballs with a capacity of 250-280 grains/minute, produce specifications using an electric engine drive with a power of 1 HP with a speed of 1440 rpm. The source of the forces acting on the shaft is the pulling force on the belt. The engine transmission system uses pulleys with an outer diameter of 2 inches and 9 inches that connect the motor to the connecting shaft with v-belt type A no 38, from the connecting shaft to the cutter with 2 pulleys with a diameter of 3 inches using a v-belt no 20, then pulleys connecting the connecting shaft with the stirrer shaft with a size of 3 inches and 7 inches using v-belt type A no 42. For the size of the connecting shaft with a diameter of 25.04 mm.Keywords: meatballs, shaft, pulleys, v-belt